Internal Security Act 1960: violation of human rights / Nurasyikin Ja'alam, Norfariza Ridzuan and Noradila Ab. Latif - Ja'alam, Nurasyikin; Ridzuan, Norfariza; Ab. Latif, Noradila (2007)
This research mainly consists of three parts. The first part will deal with the violation of human rights. We will determine whether ISA breaches the Article 5(3) of the Federal Constitution. The condition of the detention place will be measured using the United Nation Standard Minimum Rules for the Treatment of Prisoners. The violations of human rights also will be look into the treatment received by the detainees. The second part will deal with the misuse of the ISA by the government The government have use ISA as a tool of political oppression. The misuse of the ISA will be analyzed through several of decided cases. The abuse in the treatment will also be highlighted in this part. The last part will imposed several recommendations to improve the ISA. These recommendations were to avoid the violation of detainees' human rights and misuse of ISA by the minister. Recommendations imposed in this part will concern with the detentions under ISA and the actions of the minister or his officer in dealing with ISA. An independent body or tribunal that regulates the ISA should be established. This research is a library based research. Internet becomes our vital tool to dig in the information. We also did public interview to discover the knowledge of the public about ISA. We have interview Prof. Shad Saleem Faruqi in order to get an expert's opinion in completing our research.